Implementasi Green Business dalam Ekoturisme di Jawa Tengah (Studi pada Tiga Obyek Wisata) - Sentot Suciarto; Agatha Ferijani (JEMAP, 2020)
In the year 2025 it is hoped that ASEAN will become tourist destination offering ASEAN experience which unique, diversify, and developing sustainable, inclusive, and responsible tourism. It will become significant contributionto the economic life of ASEAN community. According to that vision, Indonesia also develops tourism which environment friendly and green business. Ecoturism as traveling activities to destination region should folow natural rules for enjoying natural beauty, including education-comprehension and support to conservation which could increase local community income. In this research selected three tourist ecotourism destination including Morosari Mangrove Forest at Demak Region, Tlogo Tuntang Tourism at Bawen Salatiga, and Forest Park Botanical Garden Mangkunegoro 1 at  Lawu Mountain at Karanganyar Region. Research result showed that Mangrove Forest Demak, Tlogo Resort Tuntang and  Forest Park Botanical Garden not yet becoming ecotourism and tourist business which profitable and sustainable tourism. There is local management desire to make tourism based on natural wealth or tourist destination which conserving ecology.  The three tourist destinations generally need continous improvement so that becoming intereseting ecoturism and profitable. It is needed to continuously conserve flora and fauna, and environment management to attract visitors.